Navigating Standardized Spaces in Student Teaching. Issue 3 (3rd July 2019) - Buchanan, Rebecca; Byard, Tessa; Ferguson, Grace; Billings, Kayla; Dana, Mingwun; Champagne, Josie
Abstract: Standardization and accountability forces in education have created a landscape that prioritizes surveillance and treats teaching and learning as transactional. This article explores how a teacher educator and student teachers sought to navigate these constrained spaces by centralizing tensions and acting agentively. Student teachers reflect on what tactics they used to address diverse learning needs, adapt scripted curricula, negotiate parent conflict, develop authentic learning experiences, and use constructivist and sociocultural learning approaches in traditional classrooms.